The effects of thermal conductivity on photovoltaic thermal collector sheet in tube type - Mohd Rosli, Mohd Afzanizam; Misha, Suhaimi; Sopian, Kamaruzzaman; Mat, Sohif; Sulaiman, M. Yusof; Salleh, Elias @ Ilias (IDOSI Publications, 2014)
Photovoltaic thermal is the device produced heat and electricity simultaneously. Consisted of photovoltaic module, collector, insulator in a single unit made the efficiency based on varied factors. For the thermal efficiency, the collector of the PVT is the crucial factor in determined a good results. In this study, the polymer and aluminum collector have been investigated to see the effect of the fin efficiency and collector efficiency factor. Knowing the fin efficiency and collector efficiency factor will be increase with the high thermal conductivity, this study observed the varied dimensions and gaps of tubes. The selected diameters were 6 mm, 12 mm and 18 mm and the gaps from 1 to 10 mm. It clearly showed the higher collector efficiency factor obtained for very small gaps for polymer. The increment width of tubes reduced the collector efficiency factor for both materials. The polymer collector reduce tremendously compared the aluminum collector. The efficiency collector factor for polymer and aluminum approximately 0.75 to 0.97 and 0.96 to 0.98 respectively. Therefore, to obtain the characteristics of polymer material such as light, cost effective and manufacturability, the small gaps of tubes can be implement as a collector without ignored the efficiency collector factor.